Multitrophic interactions among Western Corn Rootworm, Glomus intraradices and microbial communities in the rhizosphere and endorhiza of maize - Dematheis, Flavia; Kurtz, Benedikt; Vidal, Stefan; Smalla, Kornelia (Frontiers in Microbiology, 2013)
The complex interactions among the maize pest Western Corn Rootworm (WCR), Glomus intraradices (GI - recently renamed Rhizophagus intraradices) and the microbial communities in both rhizosphere and endorhiza of maize have been investigated in view of new pest control strategies. In a greenhouse experiment, different maize treatments were established: C (control plants), W (plants inoculated with WCR), G (plants inoculated with GI), GW (plants inoculated with GI and WCR). After 20 days of WCR root feeding, larval fitness was measured. Dominant arbuscular mycorrhizal fungi (AMFs) in soil and maize endorhiza were analysed by cloning of 18S rRNA gene fragments of AMFs, restriction fragment length polymorphism and sequencing. Bacterial and fungal communities in the rhizosphere and endorhiza were investigated by denaturing gradient gel electrophoresis of ITS and 16S rRNA gene fragments, PCR amplified from total community DNA, respectively. GI reduced significantly WCR larval development and affected the naturally occurring endophytic AMFs and bacteria. WCR root feeding influenced the endophytic bacteria as well. GI can be used in integrated pest management programs, rendering WCR larvae more susceptible to predation by natural enemies. The mechanisms behind the interaction between GI and WCR remain unknown. However, our data suggested that GI might act indirectly via plant-mediated mechanisms influencing the endophytic microbial communities.